Analisis Kuantitatif Komponen Autentifikasi Rekam Medis Elektronik Pada Pasien Rawat Jalan Rumah Sakit Swasta Di Cirebon - Regita Widi Cahyani; Loura Weryco Latupeirissa; Akhmad Fauzi; Husni Hidayat Malik (Jurnal Kesehatan Mahardika, 2025)
Introduction: Electronic medical records (EMR) play a crucial role in supporting effective, accurate, and legally binding healthcare services, one of which is through the completeness of authentication components. Incomplete authentication can impact the quality of service, the legal validity of documents, and hospital administration processes. Objective: This study aims to determine the level of completeness of authentication components in outpatient electronic medical records at Muhammadiyah Hospital Cirebon. Method: The study used a quantitative descriptive design with an observation method of 87 electronic medical record documents from January–March 2025 using a checklist. The authentication components analyzed included the doctor's name, barcode or doctor's signature, and date of service. Results: The results showed that 71.3% of electronic medical record documents had complete authentication, while 28.7% were incomplete. The doctor's name and barcode or doctor's signature components had a completeness level of 100%, while the date of service only reached 71.8%. Conclusion: The conclusion of the study shows that the completeness of authentication in electronic medical records has not fully met the standards, so it is necessary to increase the compliance of Professional Care Providers in completing authentication in order to improve the quality of documentation and hospital services.